Qualidade Física e Sensorial de Grãos de Coffea Canephora Pierre ex. Froehner de Diferentes Ambientes - Drumond Neto, Antonio Pereira (2017)
With the publication of the first protocol for the tasting of the coffee beverage Coffea canephora, the possibility of identifying and registering a possible diversity of the sensorial characteristics of this species has aroused the interest of producing